Radiological and Clinical Outcome of Volar Barton Distal Radius Fractures Treated by Variable Angle Volar Locking- Plates (Chinese Version) - Muhammad Ali,Zahid Hafeez, Manqoosh Ur Rehman, Shaukat Rabbani, Muhammad Saleem, Aleena Younas, Muhammad Ali,Zahid Hafeez, Manqoosh Ur Rehman, Shaukat Rabbani, Muhammad Saleem, Aleena Younas (Journal of Rawalpindi Medical College, 2019)
Background: To evaluate the functional and radiological results of treating volar Barton fractures of the distal radius with the variable Angle Volar Locking Plates (Chinese version). Methods: In this prospective study patients(n=50), of volar Barton fractures, which were fixed with Variable Angle Volar Locking Plates (Chinese version) were evaluated. Short arm back splint was applied . Volar approach was used for distal radius. After sweeping away the FPL muscle belly and retracting it ulnarly, pronator quadratus was exposed and released from its radial attachment in L shaped fashion using scalpel. Under direct visualization and with the aid of fluoroscopy, the fracture was then reduced. Plate was initially secured proximally with a 3.5-mm cortical screw in the oval hole of plate. Distal fixation with locking screws was then performed while maintaining the reduction. Radiological outcome (residual dorsal angulation, radial shortening and loss of radial inclination) was assessed according to Lidstorm criteria and clinical outcome was done using Mayo score . Results: Forty five cases were caused by road traffic accident and five cases were of domestic fall. Majority (n=28) sustained B3.1. Majority of the patients were operated within the first week of injury (60%). Mean time for radiological union was 08 weeks (6-12 weeks).Duration of hospital stay ranged from 2 to 3 days. Forty-six patients had excellent functional score at the end of six months. Forty-three patients (86%)had volar tilt in the range of 6-11 degrees and 2 patients (4%) had volar tilt in the range of 11-15 degree.Radiologically 96% patients had excellent to good results. Conclusion: Volar Barton fracture are best treated with osteosynthesis using variable angle volar locking plates